Could Lipoprotein Lipase Play a Role in Alzheimer's Disease? - Jean-Francois Blain; Judes Poirier (The Scientific World Journal)
This paper reviews recent literature on the role of lipoprotein lipase in the central nervous system with a focus on its recently described role in synaptic remodeling. This novel role could have implication for Alzheimer's disease treatment.